2009
DOI: 10.1056/nejmoa0807521
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster-Randomized Effectiveness Trial of Vi Typhoid Vaccine in India

Abstract: The Vi vaccine was effective in young children and protected unvaccinated neighbors of Vi vaccinees. The potential for combined direct and indirect protection by Vi vaccine should be considered in future deliberations about introducing this vaccine in areas where typhoid fever is endemic. (ClinicalTrials.gov number, NCT00125008.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
201
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(208 citation statements)
references
References 21 publications
3
201
1
3
Order By: Relevance
“…The role of the humoral immune response is not as well defined. Many large-scale field trials have demonstrated that S. Typhi-specific antibodies are produced in a majority of subjects following vaccination or natural illness, but the function or mechanism of protection provided by S. Typhi-specific antibodies is currently uncharacterized (8,14,23,24,31,32,39,46). A better understanding of the function of antibodies mounted in response to disease or vaccination addresses major challenges in understanding humoral immune responses to typhoid disease and aids in the evaluation of new typhoid vaccines.…”
mentioning
confidence: 99%
“…The role of the humoral immune response is not as well defined. Many large-scale field trials have demonstrated that S. Typhi-specific antibodies are produced in a majority of subjects following vaccination or natural illness, but the function or mechanism of protection provided by S. Typhi-specific antibodies is currently uncharacterized (8,14,23,24,31,32,39,46). A better understanding of the function of antibodies mounted in response to disease or vaccination addresses major challenges in understanding humoral immune responses to typhoid disease and aids in the evaluation of new typhoid vaccines.…”
mentioning
confidence: 99%
“…Inter-individual variability in immune response to peptide vaccines has been documented and a number of polymorphic loci in genes related to both innate and adaptive immune systems have been found to be associated with antibody response to vaccines (Sur et al 2009). However, little is known about genomics of immune response for polysaccharide vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of variation in immune response has been extensively studied for some vaccines. Primary failure, as assessed by post-vaccination antibody levels, occurs in a significant proportion of vaccinees; for example, 2-10% for measles vaccine (Poland 1998;Poland et al 1999), 5-20% for hepatitis B vaccine (Milich and Leroux-Roels 2003;Zuckerman 1996), and 23-40% for typhoid vaccine (Gupta et al 2008;Sur et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Corresponding serological assays have been developed and provide correlates of protection to support vaccine licensure. Both injectable and oral typhoid vaccines can provide herd protection when vaccine coverage is adequate [38][39][40]. Because Vi polysaccharide alone, as for other carbohydrate vaccines, is not effective in inducing T-cell-dependent memory responses in young infants, a conjugate vaccine composed of Vi capsular polysaccharide covalently linked to a mutant from Pseudomonas aeruginosa exoprotein A (VirEPA) was developed [41].…”
Section: Typhoid Fever Vaccinesmentioning
confidence: 99%